Genetic T-type calcium channelopathies - Weiss, Norbert; Zamponi, Gerald W (Journal of medical genetics, 2020)
T-type channels are low-voltage-activated calcium channels that contribute to a variety of cellular and physiological functions, including neuronal excitability, hormone and neurotransmitter release as well as developmental aspects. Several human conditions including epilepsy, autism spectrum disorders, schizophrenia, motor neuron disorders and aldosteronism have been traced to variations in genes encoding T-type channels. In this short review, we present the genetics of T-type channels with an emphasis on structure-function relationships and associated channelopathies.
Keywords: aldosteronism; Humans; Mutation; channelopathies; kanálopatie; zvířata; calcium channels; mutation; schizophrenia; amyotrophic lateral sclerosis; Channelopathies; vápníkové kanály; epilepsy; cav3 channels; t-type channels; Animals; lidé; mutace; Calcium Channels; autism spectrum disorders